Предмет: Алгебра,
автор: Qwerty26021999
№ 1)
Упростите выражение:
(5+m)^2+(m-2)(m+2)-2m(m+5)
№2)
Упростите выражение:
(x-2)^2-(x-1)(x+2)
Ответы
Автор ответа:
0
10+ 2м +м^2 - 4 -2м^2 - 10м = -м^2 - 8м + 6 = м^2 - 8м + 6
Х^2-4х+ 4 -х^2 -2х + х + 2= -5х+ 6
Х^2-4х+ 4 -х^2 -2х + х + 2= -5х+ 6
Автор ответа:
0
1) 10м+2м+(м*+2м)-(2м+4)-2м*+10м=12м+м*+2м-2м-4-2м*+10м=22м-м*-4. *-квадрат
2) 2х-4-(х*+2х)-(х+2)=2х-4-х*-2х-х-2=-6-х*-х. *-квадрат
Похожие вопросы
Предмет: Қазақ тiлi,
автор: zhanerkeqe75
Предмет: Алгебра,
автор: Аноним
Предмет: Математика,
автор: adletpro21
Предмет: История,
автор: blablanla